ANALISIS KINERJA PEMERINTAH DESA UNTUK PEMBANGUNAN INFRASTRUKTUR JALAN USAHA TANI DI DESA MATARAH KECAMATAN DUSUN TIMUR KABUPATEN BARITO TIMUR - Budi Setiawati; Ahmad Farhani (stiatabalong.ac.id, 2019)
The purpose of this research is to find out and analyze the performance Government of the village for the construction of road infrastructure Farmer in the village of Dusun Matarah East Barito Regency East. as well as to know and analyze the factors that hamper the performance Government of the village for the construction of road infrastructure Farmer in the village of Dusun Matarah East Barito Regency East. This study used a qualitative research approach is descriptive in nature. Techniques of data collection, through interviews and documentation. Key informants include PJ village chief, head of Government Affairs and development, Chairman of the BPD, and two communities. Interactive model of data analysis techniques belonging to Miles, Huberman and Saldana. The results of this study showed that the Government's Performance, the village of Dusun Matarah East Barito Regency East in the construction of road infrastructure Farmer during this already well underway, based on indicators: productivity, Responsiveness, Corporate Responsibility, Accountability. Factors that hinder the performance of the Government in the development of road infrastructure Village Farmer is: Internal factors; The lack of ability of Government HR village, the rising prices of materials. External Factors; The lack of participation of the community, the existence of a society that does not support the construction of road infrastructure farmer. Based on the research results, it is recommended to the Government of the village, and the public needs to be done coaching and training in the form of an increase in the ability of the Government apparatus HR village, The village government need to hold more socialization to provide insight into the mindset of the community, namely, the need to support the development of this farmer road to the welfare of society itself, to community need awareness of yourself to participate in the construction of road infrastructure, for achievement of a farmer a progress. Keywords : The Government's Performance; The Village; The Construction Of Infrastructure